Peningkatan Kualitas Pengajaran Gambar Teknik Melalui Pelatihan Solidworks Bagi Guru Sekolah Menengah Kejuruan Muhammadiyah Kabupaten Banyumas - Muhammad Muryanto; Trio Nur wibowo; Syaukaty Yasinta; Muhammad Ramadhani S. L; Irfauji Firman Hidayat (LPPM Universitas Harapan Bangsa Purwokerto, 2025)
Technical drawing training based on ISO standards using SolidWorks is a strategic step to enhance the competencies of vocational high school (SMK) teachers, particularly in aligning the learning process with industrial needs. This community service activity aimed to provide practical knowledge and skills to SMK Muhammadiyah teachers in Banyumas Regency regarding internationally standardized technical drawing (ISO 128, ISO 5456, ISO 7200) and its implementation through parametric Computer-Aided Design (CAD) software, namely SolidWorks. The training methods included lectures, hands-on practice, group discussions, pre-tests, and post-tests. The pre-test results showed that the participants' average score was only 47.5, indicating a low level of understanding of technical drawing standards and the use of SolidWorks. However, after the training, the average score increased significantly to 79.6, reflecting a 67.5% improvement. These findings demonstrate that training based on hands-on practice and case studies can effectively enhance teachers' technical competencies. This program also strengthens the role of teachers as agents of change in vocational education based on Industry 4.0 technology. It is hoped that this activity will be followed by advanced training sessions, such as motion simulation and stress analysis using CAD.